Impact of Expansionary Austerity Policy on GDP: Egypt - Mandour, Ahmed; Hamieh, Tahira; Abdel Azim , Mohamed (The Arab Journal of Administration, 2021)
The study aims to test the hypothesis of expansionary austerity in the Egyptian economy, ie to measure the impact of fiscal austerity policies in the Egyptian economy on the growth of the Egyptian economy. To test the validity of this hypothesis, the economic growth equation in the Egyptian economy was estimated. Annual data were used for the period (1980-2017),The single equation model was relied on by using a multiple regression equation for economic growth. The determinants of economic growth that have been used as independent explanatory variables for the model are: private consumption expenditure, private investment spending, government spending in both consumption and consumption, net dealing with the outside world, taxes, The root of the unit was tested to determine the stability of the time series using the Philip Peron test. The results of the Philip Peron test showed that all the time series of real GDP, real private consumption expenditure, real private investment spending, real government spending in both investment and private sectors and net dealing with the outside world and the labour force stable When taking the first differences, either assuming intercept or intercept and trend, at the level of significance of 1%. The study also concluded that expansionary fiscal austerity is not effective in stimulating real GDP in the Egyptian economy. This may be due to the fact that government spending in the Egyptian economy focuses on infrastructure, which reduces the impact of crowding out the government sector to the private sector, in addition to the existence of idle resources. In the Egyptian economy, this means that high government spending is a catalyst for economic growth in the Egyptian economy and hence the ineffectiveness of expansionary policies in the Egyptian economy.